Establishment of Design Strategies and Design Models of Human Computer Interaction Interface Based on User Experience - Gong, Chao; Qiu, Yue; Zhao, Bin (Design, User Experience, and Usability: Theory and Practice, 2018)
Taken into consideration people’s demand for access to information in nowadays society, the paper carries a systematic analysis and a detailed study of designing human-computer interaction interface by theoretical analysis and integration thereof combined with practical experience. The paper puts forward reasonable and practical design strategies, establishes relatively complete and systematic software interface design models, and makes rewarding suggestions on the future of software interface design. First, the paper delves into the subject of the interactive process, human, namely users, and sets up the model of user analysis. The essay studies and analyzes relevant design strategies based on the users’ perceptive, cognitive, emotional ability towards information and the characteristics of the user experience in the process of human-computer interaction, proposes design strategies of human-computer interaction interface based on users’ perception, cognition, emotion of information and the characteristics of the user experience. Also, user-centeredness is established as the fundamental research ideology. Then, characteristics of information identification in software interaction interfaces are summarized. Principles of interface design for information representation and recognition is proposed, and the subject of the design of software interaction interface is determined. Further, the paper presents specific methods in which designs can be implemented. It develops a systematic model of the integral design of the software interface, summarizes principles of software interface design based on the characteristics of interface. The integral design model mainly comprises of the following phases: demand analysis, implementation, testing and evaluation. It puts forward the demand of “iteration” throughout the designing process. What is more, the optimization theory of “three transformation and fusion” of software interaction interface design is proposed. Last but not the least, the paper puts forward the goals of future software interface design, that is, “generalization”, “intelligentization” and “actualization” and raises relevant opinions and suggestions thereof. The research provides a practical and valuable reference for software interaction interface design in the future.